2010
DOI: 10.1111/j.1365-2338.2010.02416.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐laboratory validation of PCR‐based protocol for detection of olive viruses

Abstract: Sanitary selection and certification of olive cultivars require sensitive diagnostic methods and effective sanitation protocols. Although much attention has been paid in the past few years to the development of diagnostic tools for reliable virus identification, the need to define a common and standardized diagnostic protocol led to the implementation of a ring test among nine Italian diagnostic laboratories. A one‐step RT‐PCR protocol and different primer sets, targeting the most common olive viruses covered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…This result is extremely important as TNA has been widely used as template for RT-PCR in olive surveys and shows the importance of sequencing. Despite the fact that TNA extracted by using commercial kits show better results (Loconsole et al 2010), the use of dsRNA as template in RT-PCR has previously shown to give more accurate results (Felix et al 2012), because it allows the use of a larger and more representative sample, reducing the constraints of low viral concentration and uneven distribution (Varanda et al 2010(Varanda et al , 2014. In addition it allows the elimination of virus non-related nucleic acids that interfere in the viral genome amplifications (Bertolini et al 2003;Luigi et al 2011) which revealed to be a problem when TNA was used as template in RT-PCR in this study.…”
Section: Discussionmentioning
confidence: 97%
“…This result is extremely important as TNA has been widely used as template for RT-PCR in olive surveys and shows the importance of sequencing. Despite the fact that TNA extracted by using commercial kits show better results (Loconsole et al 2010), the use of dsRNA as template in RT-PCR has previously shown to give more accurate results (Felix et al 2012), because it allows the use of a larger and more representative sample, reducing the constraints of low viral concentration and uneven distribution (Varanda et al 2010(Varanda et al , 2014. In addition it allows the elimination of virus non-related nucleic acids that interfere in the viral genome amplifications (Bertolini et al 2003;Luigi et al 2011) which revealed to be a problem when TNA was used as template in RT-PCR in this study.…”
Section: Discussionmentioning
confidence: 97%
“…The partial genome information available for OLYaV (NC_043417) corresponds to only 4605 nucleotides containing partial ORF1b (RdRp), ORF2 (21kDa), ORF3 (7kDa), ORF4 (HSP70h) and the 5′-end of ORF 5 (HSP90h) [ 2 ], and a subsequent extension of 854 nucleotides in the HSP90h gene towards the 3′-end (AJ844555) [ 3 ]. The development and application of diagnostic methods by RT-PCR of specific regions of the HSP70 gene [ 1 , 4 ] has revealed that OLYaV is one of the most widespread olive viruses with different levels of incidence: California (USA) (93%) [ 5 ], Italy (64–21%) [ 6 , 7 , 8 ], Tunisia (49%) [ 9 ], Lebanon (24%) [ 10 ], Syria (15%) [ 11 ], Greece (5%) [ 12 ] and Albania (2%) [ 13 ]. In addition, studies of OLYaV HSP70 gene diversity revealed a high divergence in this region of samples collected in clonal germplasm repositories in California and Greece [ 5 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a one step RT-PCR protocol has been set up and validated in an inter-laboratory ring test (Loconsole et al, 2010) for the diagnosis of the eight most important olive viruses. This should be a starting point for anyone wishing to approach the sanitary selection of olive plants.…”
Section: Identification Of Olive Pathogens: Updates On Diagnostic Toolsmentioning
confidence: 99%